Perluasan Jaringan Pemasaran melalui Kemitraan dengan Marketplace bagi PKL Dampak Relokasi Pemkot Surakarta - Nadia Sigi Prameswari; Pratama Bayu Widagdo; Eko Sugiarto (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2019)
Street Vendors (PKL) are considered to cause chaos in the city of Surakarta because it makes slums and causes congestion. In order to preserve the beauty of the city, street vendors are being targeted by the Surakarta City Government. This condition creates new problems for street vendors because of the loss of customers and the low number of visitor anemos because most people do not know about the existence of new shanties after relocation. The solution that can be taken from these problems is through marketing innovation training and promotion strategies for street vendors, including: (1) training and mentoring focusing on marketing innovation strategies, including: partnerships with marketplace / e-commerce culinary products, (2) alternative design programs promotion in accordance with the target market, and promotion in social media, and (3) training in promotion strategies through designing visual identity designs that are applied to various media, such as booths / carts, product packaging, product design, uniforms and online promotional media. The method used is training and assistance with a collaborative participatory approach. The long-term outcome expected from this service is the expansion of marketing networks, increasing income and welfare of street vendors through marketing innovation and promotion.